Drip water Geochemistry of Niah Great Cave, NW Borneo, Malaysia: a base line study - Prasanna, Mohan Viswanathan; Ramasamy, Nagarajan; Chidambaram, S.; Manikandan, S.; Aruchunan, Elayaraja (Springer, 2014)
A base line study was conducted to understand the geochemical variations of drip waters in Niah Great Cave, Sarawak, NW Borneo of Malaysia. Drip waters were collected at three different sites within the cave (D6: SW entrance enroute to painted Cave; D5: centre of the Great Cave, and D8: west mouth Great Cave entrance). The collected samples were analysed for temperature, pH, EC, major elements, non purgeable organic carbon, δ13C and δ18O. Mg/Ca and Sr/Ca ratios, ionic strength, partial pressure of CO2 and saturation indices of carbonate minerals have been used to dictate the geochemical signatures of drip water compositions. The data reveal a wide range of major ion chemistry at three different sites within the cave. The δ13C values in drip waters range from −10.58 to −10.09 ‰. The enriched and the depleted δ13C values are noted at the entrances of the cave due to degassing of water CO2 and warmer air results in lighter fractions of δ13C. The δ18O values range from −6.89 to –6.16 ‰. Minor δ18O deviation in the drip waters are due to the variation in drip rates as faster drip rates show depleted isotopic composition and vice versa. The spatial variability of drip water chemistry results due to water–rock interaction at various conditions of subsurface flow path. This study gives a basis for interpreting the varying controls on drip water chemistry in the cave.